A Complete Active Space Self-Consistent Field and Density Functional Theory Study of S0, T1, S1 States of Five Phenol ortho-Derivatives - Wu*, Chengguo; Gong, Yanchun; He, Suhong; Dai, Binfei; Huang, Yanhua (Asian Journal of Chemistry, 2014)
The low-lying electronic states (S0, S1 and T1) of five phenol ortho-derivatives have been studied by the complete active space self-consistent field (CASSCF) and B3LYP methods. Structure optimizations indicate that the S1 structures of 2-nitrophenol, salicylaldehyde, 2-acetylphenol are H transfer structures, but those of salicylamide and salicylic acid not. The T1 structures are all H transfer structures. To these five phenol ortho-derivatives, all the transitions of S0®S1 and S0®T1 are come from the HOMO to LUMO orbital, and show p-p* transition characters. Additionally, ortho-effect is also discussed.